Programa de bilingüismo en colombia: el uso de la traducción en los libros didácticos de inglés como lengua extranjera - Franco, Edwin Leonardo Barrera (2018)
Colombia and the United States have had a history of close bilateral relationship; this fact has left the Ministry of Colombian National Education (MEN) with the difficult task to improve the English proficiency in the country, actually the MEN has work since the 1980s to achieve this goal. Nevertheless, Colombia has register low level of English proficiency in recent national and international tests. As a result, in 2004, the "Bilingualism Program" was institutionalized with a policy structured on the Common European Framework (CEFR) and formalized on July 12, 2013, when it received the full support of the National Government through the Bilingualism law. Finally, in 2016, the material English please fast track was created through an agreement between the (MEN) and the British Council, for teaching English in the country's secondary education. Some characteristics of this material have not yet been analyzed, one of them is the use of translation as a complement of language teaching. Consequently, this research aims to analyze the translation exercises included in the material under the light of the functionalist theory of Christiane Nord (2012, 2010, 2009), Reiss and Vermeer (1996). The functionalist view allows exploring this area of teaching from a different perspective, mainly because the German theory analyzes inter/extra textual elements surrounding the text to be translated. This analysis allows an interaction and understanding not only in the idiomatic field, but also in the learning of cultural aspects. The latter is of high relevance, as it is fundamental when it comes to teaching a foreign language with a communicative basis. Thus, based on the functionalist proposal, it was evident that the translation exercises analyzed lacked sufficient information regarding place, gender, time, functions of the source text and the cultures involved in the process to generate a real communicative act. In response, the functionalist theory presents a detailed guide to the pre-translational process that will help English teachers design and evaluate functional translation materials with clear and structured tasks to achieve communicative purposes for students. Our tentative is to showcase in the translation proposals put forward in this paper.